A Nodulation-Proficient Nonrhizobial Inhabitant of Pueraria phaseoloides - W. M. M. Wedage; A. H. M. N. R. Aberathne; I. N. Harischandra; D. Gunawardana (The Scientific World Journal)
Pueraria phaseoloides is a legume cover crop, found chiefly in the wet zone of Sri Lanka. Nitrogen fixation is performed by nodular inhabitants of this cover crop, comparable to the nodule-dwelling bacteria of most other legume plants. We isolated a bacterium (Sub1) from Pueraria phaseoloides, of coccobacillus cell shape, that showed nodulation, when assessed by hydroponics, showing nodules as early as 3 weeks after reinfection. When a nifH fragment from the genome of this bacterium was amplified using a pair of nifH primers, it yielded an amplicon of 360 bp that, when sequenced, helped us identify the bacterium, as belonging to a species of Pseudacidovorax intermedius, at 99% sequence identity. When we constructed a phylogenetic tree with neighboring sequences, we encountered nifH sequences of Pseudacidovorax, forming a monophyletic cluster, which too contained a single Azospirillum species. The genus Pseudacidovorax is a bacterium that, so far, has not been associated with legume nodules. Sub1 secreted a pair of enzymes to the extracellular medium to degrade cellulose and milk proteins. The Sub1 bacterium showed biofilm formation and secreted into the extracellular medium, indole acetic acid. Sub1 also showed a “bulls eye” swarming pattern for the chemoattractant proline, while showing no significant chemotaxis movement, for naringenin, quercetin, and glutamate. Sub1 too possesses the basic genetic foundation (nifH and nifD) to produce a molybdenum-dependent nitrogenase enzyme. We finally show that this rare nonrhizobial bacterium is able to impact, positively, nodulation and shoot length of Pueraria plants, demonstrating that this beta-proteobacterium can abet the biological vigor of this legume cover crop.